1998
DOI: 10.1007/s11661-998-1017-x
|View full text |Cite
|
Sign up to set email alerts
|

Warm-temperature tensile ductility in Al−Mg alloys

Abstract: Several binary and ternary Al alloys containing from 2.8 to 5.5 wt pct Mg were tested in tension at elevated temperatures (200 ЊC to 500 ЊC) over a range of strain rates (10 Ϫ4 to 2.0 s Ϫ1 ). Tensile ductilities of up to 325 pct were obtained in binary Al-Mg alloys with coarse grains deformed in the solute-drag creep regime. Under test conditions in which solute-drag creep controls deformation, Mg in concentrations from 2.8 to 5.5 wt pct neither affects tensile ductility nor influences strain-rate sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…Binary Al-Mg alloys containing from 2.2 up to 10 wt% Mg have been shown to exhibit stress exponents of nϷ3 and apparent activation energies of about 136 kJ/mol in this temperature and strain rate regime, values which are indicative of solute-drag control of creep [33]. However, recent work [34,35] has demonstrated that ter- nary additions of 0.25 wt% Mn, or more, in Al-MgMn alloys result in an increase in the stress exponent to a value of between 4 and 5 while activation energy values remain at about 140 kJ/mol. The increase in the stress exponent, n, to a value similar to that for pure metal behavior has been attributed to an effective reduction of Mg content due to interaction between the Mg and Mn solutes [34].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Binary Al-Mg alloys containing from 2.2 up to 10 wt% Mg have been shown to exhibit stress exponents of nϷ3 and apparent activation energies of about 136 kJ/mol in this temperature and strain rate regime, values which are indicative of solute-drag control of creep [33]. However, recent work [34,35] has demonstrated that ter- nary additions of 0.25 wt% Mn, or more, in Al-MgMn alloys result in an increase in the stress exponent to a value of between 4 and 5 while activation energy values remain at about 140 kJ/mol. The increase in the stress exponent, n, to a value similar to that for pure metal behavior has been attributed to an effective reduction of Mg content due to interaction between the Mg and Mn solutes [34].…”
Section: Resultsmentioning
confidence: 98%
“…However, recent work [34,35] has demonstrated that ter- nary additions of 0.25 wt% Mn, or more, in Al-MgMn alloys result in an increase in the stress exponent to a value of between 4 and 5 while activation energy values remain at about 140 kJ/mol. The increase in the stress exponent, n, to a value similar to that for pure metal behavior has been attributed to an effective reduction of Mg content due to interaction between the Mg and Mn solutes [34]. Elongations to failure data obtained here are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For coarse grained Al-Mg alloys deformed in the viscous glide regime, values for the maximum strain in excess of 300% can be obtained [56,57,58]. Such elongations are close to those found in conventional superplasticity of fine-grained Al-Mg alloys and are sufficient for many practical applications.…”
Section: In Situ Tem Straining and Heating: Superplasticitymentioning
confidence: 64%
“…Therefore if the dominant deformation mechanism is the Class I creep, the relation to Q Mg should be discussed. 3,11,12) Sherby and Wadsworth 13) found that the activation energy at n = 2 was equal to about 135-139 kJ/mol while that at n = 3 was equal to about 137-142 kJ/mol in a fine grained Al-5%Mg-1.2%Cr alloy. They concluded that the slip process (dislocation creep) observed in the alloy including second phase particles was identical to that observed in Al-Mg solid solution alloys.…”
Section: Temperature Dependencementioning
confidence: 99%
“…1) In Class I type alloys such as Al-Mg or Al-Cu base alloys, fairly large elongations have been observed at high temperatures even for coarse-grained samples. [2][3][4] It is recently called 'Class I superplasticity'. 5) This superplasticity has a merit of less cavitation because main deformation mechanism is not grain boundary sliding.…”
Section: Introductionmentioning
confidence: 99%